Alegebra liner equations.

1) using the table of ordered pairs which equation shows the linear relationship between the x and y values
X Y
-2 4
1 -2
3 -6

A) y = x + 2
B) y = x - 2
C) y = 2x
D) y = -2x

2) what is the equation in slope intercept form of the line that contains the points (3 , -4) and (5 , -6)
X. Y
3 -4
5 -6

A) y = -x - 1
B) y = -x + 2
C) y = x - 1
D) y = x + 1

3) which phrase describes the linear relationship between x and y
X Y
1 2
2 4
3. 5

A) y is 2 times x
B) x is 2 times y
C) y is 2 less than x
D) y is 2 more than x

4 which of the following equations shows the linear relationship between the x and y variables shown in the table of ordered pairs.
X. Y
2 7
3 8
4 9

A) y = x - 5
B) y = x + 5
C) y = 5 - x
D) y = 5x

5) which phrase describes the linear relationship between the x and y values in this table?
X. Y
3 9
4 12
5 15

A) x is 3 times y
B) y is 3 times x
C) y is 3 less than x
D) y is 3 more than x

6)which phrase describes the linear relationship between the x and y values shown in the table?
X. Y
8 2
9 3
10 4

A)y is 6 times x
B) x is 6 times y
C) y is 6 less than x
D) y is more than x

Respuesta :

1. The answer would be (D). This is because you will plug is the (x) of the ordered pair into the equation(y=-2x), so first off would be (y=-2(-2)). since your multiplying a negative time a negative, you will get your (y) which is 4. Now you do this with the rest. -2(1)=-2 and -2(3)=-6.
2. This would be (A). This answer is simple. First you will take one of the equations (y=-x-1) and plug x into it's place so, y=-3-1, getting your answer(y) as being -4. Now you do the same with the other pair. y=-5-1, getting -6, showing (A) as your answer.
3.The answer will be (A)y is 2 times x. this is because you wou would make out the equation from the answer (y=2x). Now knowing your equation, all thats left is plugging in your (x) factors. so y=2(1), getting your (y) value of 2 and you would do this with the rest of your x factors. 
4. y=5+x
    y=5+(2)= 7
    y=5+(3)= 8
    y=5+(4)= 9
5. (B)y is 3 times x
    y=3(x)
    y=3(3)=9
    y=3(4)=12
    y=3(5)=15
6. (C)y is 6 less than x
    y=6-(x)
    y=6-(8)=2
    y=6-(9)=3
    y=6-(10)=4

Answer:

1. The answer would be (D). This is because you will plug is the (x) of the ordered pair into the equation(y=-2x), so first off would be (y=-2(-2)). since your multiplying a negative time a negative, you will get your (y) which is 4. Now you do this with the rest. -2(1)=-2 and -2(3)=-6.

2. This would be (A). This answer is simple. First you will take one of the equations (y=-x-1) and plug x into it's place so, y=-3-1, getting your answer(y) as being -4. Now you do the same with the other pair. y=-5-1, getting -6, showing (A) as your answer.

3.The answer will be (A)y is 2 times x. this is because you wou would make out the equation from the answer (y=2x). Now knowing your equation, all thats left is plugging in your (x) factors. so y=2(1), getting your (y) value of 2 and you would do this with the rest of your x factors.  

4. y=5+x

   y=5+(2)= 7

   y=5+(3)= 8

   y=5+(4)= 9

5. (B)y is 3 times x

   y=3(x)

   y=3(3)=9

   y=3(4)=12

   y=3(5)=15

6. (C)y is 6 less than x

   y=6-(x)

   y=6-(8)=2

   y=6-(9)=3

   y=6-(10)=4

Step-by-step explanation: